Reverse Price Discrimination with Bayesian Buyers1. (June 2014) - Bang, Se Hoon; Kim, Jaesoo; Yoon, Young‐Ro
<x xml:space="preserve">Abstract</x> This paper studies price discrimination under the situation in which buyers' prior valuations are initially observable by a seller but buyers receive further information about a product or service which remains private thereafter. The buyers interpret new information via Bayes' rule. We show that, in this environment, prices are not monotone in buyers' prior valuations. Interestingly, this results in the possibility that a seller intentionally offers a higher price to a low valuation buyer rather than a high valuation buyer (Reverse Price Discrimination). We derive this result in both monopoly and duopoly markets.